Accelerated Digital Transformation and Development of Digital Talent in Local Governments under Japan's Bureaucratic Policies - Nakagawa, Go (Indonesian Association for Public Administration, 2025)
This study examines at the role of digital talent in Japan's local governments amid the COVID-19 pandemic-induced increased drive for digital transformation (DX). As local governments work to standardize their information systems by 2025, a serious scarcity of digital expertise presents a huge obstacle. The study takes a mixed-methods approach, examining both qualitative interviews and quantitative surveys performed by the Japan Municipal Research Center, which included representatives from 815 municipalities, to evaluate strategies for acquiring and nurturing digital talent. The findings show that local governments typically use two strategies: acquiring experienced IT workers and building digital knowledge among existing civil servants through extensive training. The effectiveness of these strategies varies, with some municipalities successfully improving their digital capabilities while others continue to struggle due to insufficient alignment with organizational needs and a lack of understanding of local government functions among externally recruited professionals. The study shows that, while technical abilities are required, digital talent's ability to coordinate and integrate within the municipal environment has a substantial impact on the success of DX programs. Effective digital transformation necessitates not only the recruitment of persons with strong ICT abilities, but also the development of robust coordination and negotiating skills among digital staff in order to encourage holistic governance and combine digital plans with larger municipal duties. This approach emphasizes the importance of a diverse skill set among digital talent in navigating the intricacies of public sector digitization under Japan's bureaucratic norms.